2023
DOI: 10.1002/chem.202203240
|View full text |Cite
|
Sign up to set email alerts
|

In‐line Multidimensional NMR Monitoring of Photochemical Flow Reactions

Abstract: This work demonstrates the in‐line monitoring of a flow photochemical reaction using 1D and ultrafast 2D NMR methods at high magnetic field. The reaction mixture exiting the flow reactor is flown through the NMR spectrometer and directly analyzed. In the case of simple substrates, suitable information can be obtained through 1D 1H spectra, but for molecules of higher complexity the use of 2D experiments is key to address signal overlaps and assignment issues. Here we show the usefulness of ultrafast 2D COSY ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…9). 151 UF 2D NMR was found to provide kinetic data that was in very good agreement with 1D data, while offering improved signal dispersion, thus providing an efficient and reliable approach to screen reaction conditions in organic synthesis.…”
Section: Fast 2d Nmr Methodsmentioning
confidence: 85%
“…9). 151 UF 2D NMR was found to provide kinetic data that was in very good agreement with 1D data, while offering improved signal dispersion, thus providing an efficient and reliable approach to screen reaction conditions in organic synthesis.…”
Section: Fast 2d Nmr Methodsmentioning
confidence: 85%
“…This approach has been used recently by Bazzoni et al for the in-line monitoring of flow photochemical reactions. 19 In that case, stopped flow acquisitions are appropriate, because the solution does not evolve after it exits the flow reactor. However, for the online monitoring of batch reactions, stopped-flow acquisition reduces the rate at which data can be acquired, and may break the assumption that the solution in the flow cell is representative of that in the batch reactor.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Bazzoni et al demonstrated the inline monitoring of a flow photochemical reaction using one-dimensional (1D) and ultrafast two-dimensional (2D) NMR methods in a high magnetic field. 27 The reaction mixture exiting the flow reactor flowed through the NMR spectrometer and was directly analyzed. For simple substrates, suitable information could be obtained through 1D 1 H spectra; however, for molecules of higher complexity, the use of 2D experiments was key in addressing signal overlaps and assignment issues.…”
Section: Kinetic and Thermodynamic Studiesmentioning
confidence: 99%